Analisis Strategi Bisnis dalam Peningkatan Penjualan pada Usaha Warung Kopi - Widiastuti Widiastuti; Daspar Daspar; Isarianto Isarianto; Sunita Dasman; Nadia Meirani (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2025)
The study focuses on analyzing business strategies to enhance sales in 24-hour coffee shops (warkop24h) in Indonesia, considering their unique challenges and opportunities. Conducted through supportive activities in Karangasih Village, Bekasi, the research employs various methodologies including surveys, discussions, and practical tutorials aimed at providing comprehensive reviews and innovative strategies. Key findings indicate that these coffee shops need to improve promotional efforts and address supply chain issues, particularly with essential ingredients like ice, to bolster customer satisfaction. By developing unique menu offerings and leveraging digital marketing, these businesses can capture the attention of the younger demographic, particularly Gen Z, who view warkop as social and creative spaces. The study concludes that implementing strategic adaptations in response to market trends and customer preferences can significantly bolster the viability and growth of coffee shop businesses in competitive environments. This research highlights the critical role of micro, small, and medium enterprises (UMKM) in contributing to the broader economic framework of Indonesia.